Percutaneous transluminal angioplasty of stenosed aortocoronary bypass grafts. Issue 6 (December 1984) - El Gamal, M; Bonnier, H; Michels, R; Heijman, J; Stassen, E
Abstract : During the period between October 1980 and December 1982, percutaneous transluminal angioplasty of stenosed aortocoronary bypass grafts was attempted 44 times in 31 patients who had developed disabling angina pectoris four months to seven years after coronary bypass surgery. The primary success rate was 93%. Two (4.5%) patients developed myocardial infarction related to the procedure. No emergency aortocoronary bypass surgery was required and there was no mortality. Although the primary success rate was high, the incidence of recurrence after one or more angioplasties was 50%. Despite this recurrence rate the condition of 10 of the first 16 (62%) patients was clinically improved after a mean follow up of 26 months.